International Experience and Practical Enlightenment for Ethics Education in Science and Technology - Sudan XIE; Hua CHEN (Yixue yu zhexue)
As a vital component of science and technology ethics governance, science and technology ethics education has become an important issue in contemporary discourse. The United States Japan, European Union countries have implemented relevant science and technology ethics education and have gradually established comprehensive systems of science and technology ethics education, offering pioneering practices and valuable references. The science and technology ethics education in the United States has experienced a shift from responsible research to responsible and ethical research. The science and technology ethics education in Europe focuses on the moral cultivation of researchers, while Japan promotes science and technology ethics education in the form of online education. Common features among these approaches are mainly manifested in focusing on the concept of embedded ethics education, improving teachers' ethical literacy and case-based teaching methods. These experiences offer practical insights for China, such as fostering a teaching philosophy centered on "technology for good", cultivating a high-quality teaching faculty, and promoting the digital sharing of science and technology ethics education resources.